Peran Kesenian Kuda Kosong Dalam Pelestarian Budaya Lokal Cianjur - Putra, Muhammad Andhika Nazila; Setiaji, Denden; Apriani, Arni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Traditional crafts are an important component of local cultural identity and reflect the principles, beliefs, and social structures of the community. This study investigates the role of the Kuda Kosong art in preserving local culture in Cianjur Regency. Descriptive quantitative with an ethnographic approach was used, with observation, in-depth interviews, and documentation studies. The results of the study indicate that Kuda Kosong is not only used as an art performance; it also functions as a spiritual medium, a means to teach culture, and a symbol of the community's collective identity. This art continues to live thanks to community participation, regeneration of artists, and adaptation to the times. This happens despite facing challenges such as modernization and lack of policy support. According to this study, preserving local culture requires cooperation between communities, educational institutions, and local governments.